A Predictive Fuzzy Expert System for Diagnosis of Cassava Plant Diseases (Global Journal of Science Frontier Research, 2015)
Cassava is an important tropical root cropwidely grown in many part of the world in a range of agro-ecological environments. The crop can be used for food and non-foods products. Cassava is capable of providing starch for use in drug industries, it is a stable source of dietary energy for more than 500 million. Nonetheless, despite the nutritional and economic significance of the cassava crop, the diseases incidence on cassava plantations is fast becoming a constraint in farmers' quest for a bountiful harvest. The efforts of agricultural extension agents seem not to be sufficient in tackling this menace since there is always a limit to how far the human capacity can be stretched in the face of highly demanding situations. Hence, this paper proposed the development of fuzzy expert system for predicting cassava plant disease. The system was developed with the help of fuzzy tool in MATLAB vs. 9. It employed 18 rules for the Cassava Mosaic, 27 rules for the cassava brown streak and 27 rules for cassava bacteria blightfor the classification and prediction of cassava plant diseases. This would provide immediate and instant information to the possible disease.
Keywords: cassava diseases; symptoms; prediction; fuzzy expert system; fuzzy inference system